Absolutism without Tyranny in Gorboduc: The Changing Poetics of Tudor Political Drama. Issue 2 (6th February 2017) - Majumder, Doyeeta
Abstract: Besides being the first five‐act tragedy on the English stage, Gorboduc was also the first play to depict usurpation, regicide, and rebellion, on the English stage – all of which became common plot devices in late‐sixteenth century English drama. By offering a reading of the play's treatment of absolutism – divorced from tyranny – manifesting itself in the decision upon the sovereign exception, this article will re‐evaluate the differences between early Tudor political moralities about tyranny and the late Elizabethan usurpation plays, and will ground the transition from one to the other in Gorboduc 's engagement with radical innovations in dramaturgy and political thought. It will refer to contemporary political tracts as well as modern political theory, especially the legal fiction of the 'king's two bodies' which indirectly makes its presence felt in Gorboduc . Invoking Ernst Kantorowicz's theorization of the 'king's two bodies' and Carl Schmitt's theory of sovereignty as a critical framework, this article questions the relation of sovereign power to the person of the bearer, and problematizes the notion of monarchical absolutism.